Casting wider nets: advancing women's participation in Colorado's fishing community - Teumer, Meghan, author; Lavoie, Anna, advisor; Teel, Tara, committee member; Bombaci, Sara, committee member (Colorado State University. Libraries, 2026)
Despite the growing number of women participating in outdoor recreation, there remains a significant gap in research exploring what motivates and constrains women in recreational fishing—and how they navigate these constraints. This study seeks to address this gap through in-depth qualitative interviews with ten women anglers in Colorado. Findings reveal that while some motivations align with broader trends—such as a desire for rest, connection with nature, and personal achievement—women also experience unique constraints that diverge from those documented in traditional leisure studies focused on white male participants. These include gender stereotyping, discrimination, safety concerns, lack of representation, and exclusionary social norms. Women negotiated these constraints through strategies such as embracing sense of empowerment, building women angling communities, cultivating confidence, and adapting safety practices. The results underscore the need to continue to revisit and expand the leisure constraints framework to more fully capture the intersecting identities and lived realities of underrepresented recreationists and take into consideration the unique and complex characteristics from each individual to better understand what motivates and constrains them. This research contributes critical insight to guide inclusive policy and program development aimed at supporting women's equitable participation in recreational fishing in Colorado.
Keywords: fishing; natural resources; women; leisure studies; Colorado; recreation